Analysis of product development on large-scale production with multi-criteria approach - Kostanjevec, Tomaž (Strojniški vestnik, 2009)
The multi-criteria (MC) method is applied to the development of a large-scale product in the case of mid-price range washing machines using MC approach. The concept represents the method for developing a new product in the production process. The development of a large-scale product on the basis of MC analysis provides more accurate forecasting of the most important parameters in the centrefold of a multidimensional (MD) character in the way of customer demands, and important production and development restrictions areset in this MD environment with aid of MC analysis. The production parameters are identified and through this, there is a possibility of reducing production costs. A forecasting method of production demands as possible result is powerful tool for achieving strategically and concurrent advantage.
Keywords: razvoj izdelkov; večkriterijska analiza; proizvodnja; pralni stroji